2015
DOI: 10.1002/eqe.2584
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐angle, multi‐damage fragility curves for seismic assessment of bridges

Abstract: Summary The scope of this study is to investigate the effect of the direction of seismic excitation on the fragility of an already constructed, 99‐m‐long, three‐span highway overpass. First, the investigation is performed at a component level, quantifying the sensitivity of local damage modes of individual bridge components (namely, piers, bearings, abutments, and footings) to the direction of earthquake excitation. The global vulnerability at the system level is then assessed for a given angle of incidence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…21 Several studies addressed aspects of the abutment-backfill system such as the nonlinear behaviour of its components and the formation of a gap between the abutment and the backfill (previous studies [22][23][24] among others); however, the abutments are not expected to fail under seismic actions in conventional bridge typologies. 25 Recent studies like 24 have also addressed the important issue of the uncertainties involved in the modelling of the abutment-backfill system. Pier failure was also the focus in numerical studies where bridges with rocking piers were examined, 26 assuming that the structure fails only when overturning of the piers occurs due to excessive horizontal displacement.…”
Section: Introductionmentioning
confidence: 99%
“…21 Several studies addressed aspects of the abutment-backfill system such as the nonlinear behaviour of its components and the formation of a gap between the abutment and the backfill (previous studies [22][23][24] among others); however, the abutments are not expected to fail under seismic actions in conventional bridge typologies. 25 Recent studies like 24 have also addressed the important issue of the uncertainties involved in the modelling of the abutment-backfill system. Pier failure was also the focus in numerical studies where bridges with rocking piers were examined, 26 assuming that the structure fails only when overturning of the piers occurs due to excessive horizontal displacement.…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly true in the case of skewed bridges, as the direction of seismic excitation is strongly coupled with the contribution of the excited torsional modes of vibrations and the resulting overall response. Taskari and Sextos [2015] show that ground motion directionality has a significant effect on the individual fragility of specific bridge components depending on the structural system and the damage model considered. Assessing the impact of seismic excitation directionality on the seismic response of skewed bridge may help in revealing issues regarding ground motion directionality in a specific ground motion simulation method (e.g., [Burks and Baker, 2014;Burks et al, 2015].…”
Section: Description Of Synthetic and Real Ground Motion Datasetsmentioning
confidence: 99%
“…Uncertainty related to the directionality of the incoming ground shaking, that is, the orientation of the propagating seismic wavefront with respect to a structure's axis, is often poorly investigated, despite the scientific evidence of significant sensitivity of structural response to the direction of seismic loading (e.g., [Taskari and Sextos, 2015]). As discussed in Taskari and Sextos [2015], a few studies have essentially shown that there is not a critical angle of excitation that may simultaneously trigger the most unfavorable response in all considered structural components and EDPs, either in the linear or in the nonlinear range. This also applies to bridges, and particularly skewed ones, for which the direction of seismic loading is strongly coupled with the contribution of the excited torsional modes of vibration and the resulting bridge response.…”
Section: Ground Motion Directionalitymentioning
confidence: 99%
“…10,11,14,30,36,37,42,[51][52][53]. Provided with a solid mathematical background, such methods Structures xxx (2015) xxx-xxx are not always easily approachable by practitioners and thus not necessarily appealing to the community.…”
Section: Introductionmentioning
confidence: 98%